Diagnóstico comunitario de salud del barrio Turupamba sector II, septiembre - diciembre de 2013 - Carrillo Condoy, Viviana Katherine (2014)
The present study titled " COMMUNITY DIAGNOSIS OF HEALTH DISTRICT Turupamba SECTOR II , SEPTEMBER- DECEMBER 2013 " is framed in the macro - project NURSING PARTICIPATION MODEL OF COMPREHENSIVE HEALTH CARE - MAIS HOSPITAL UNIVERSITY Motupe SEPTEMBER - DECEMBER 2013 aims to contribute to the social development of the town , bringing with statistical data that will enable them to basic health teams Motupe University Hospital , develop strategies for maintaining and improving the health of individuals , families and communities , from a biopsychosocial , multidisciplinary and intercultural approach. The study was descriptive , emphasizes the analysis and interpretation of the facts, the methodology relied on strategies established in the comprehensive care model of health, such as Home Visit to implement the Family Record and interview guide that allowed complete information to the baseline , where priority problems were identified to take appropriate technical and political decisions to the local reality seeking to optimize institutional responses and encourage community participation in improving health conditions . ( Guerrero and Slimming , 2009:4 ) . Among the more significant indicators stand as female prevalence, level of basic education, / as householders engage in activities such as domestic chores, farming , masonry, school children and adolescents in cases of malnutrition , overweight and large seen part of them study , for family planning in women of childbearing age, the rhythm method is the most widely used and compared epidemiological profile of chronic diseases protrudes Alcoholism al. Keywords: Community Health Diagnostic, Epidemiological Profile